Multiple primary malignancies and gut microbiome - Yinhang Wu; Zhanbo Qu; Zheng Wu; Jing Zhuang; Yingchen Wang; Zefeng Wang; Jian Chu; Quan Qi; Shuwen Han (BMC Cancer)
Abstract Background Multiple primary malignancies (MPM) are two or more independent primary malignancies. Recently, the relationship between microbiome and various tumors has been gradually focused on. Objective To describe the relationship between MPM patients (MPMs) and gut microbiome. Methods A total of 27 MPMs, 30 colorectal cancer patients (CRCs), and 30 healthy individuals were included to obtain metagenomic sequencing data. The knowledge graphs of gut bacteria and enteroviruses were plotted based on metagenomics. Wilcoxon rank-sum test was used to screen the characteristic gut microbiome. Results The knowledge graph of gut microbiome in MPM patients was plotted. A total of 26 different gut bacteria, including Dialister, Fecalibacterium and Mediterraneibacter, were found between MPMs and healthy individuals. Twenty gut bacteria, including Parvimonas, Dialister and Mediterraneibacter, were more abundant in MPM complicated by CRC compared with CRCs. Twenty-one different enterovirus, including Triavirus, Punavirus and Lilyvirus, were screened between MPMs and healthy individuals. Triavirus, Punavirus and Lilyvirus were less abundant in MPM than healthy individuals. The abundance of Triavirus, Punavirus and Lilyvirus in CRC patients were also lower than MPM complicated by CRC patients. Conclusion The knowledge graph of gut microbiome in MPM patients was plotted. It may provide basic data support for future research of MPM.